PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BUMI PESONA KAHYANGAN - Yohanes Very Vernando Rambe; Wijil Nugroho (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study was to determine the effect of work discipline and the quality of work motivation on employee performance at PT. BUMI PESONA KAHYANGAN. In this study, we analyzed literature and journal data, then measured it by making a questionnaire in closed questions, namely a questionnaire that had the answers provided. This study will show Work Discipline (X1) and Work Motivation (X2). The object of this research is Employee Performance (Y) and the sample is 36 employees. The method used in this research is quantitative and qualitative methods